Relativistic free-particle quantization on the light-front: New aspects - Sales, J. H.O.; Suzuki, A. T.; Zambrano, G. E.R. [UNESP] (AIP Publishing, 2004)
We use the light-front machinery to study the behavior of a relativistic free particle and obtain the quantum commutation relations from the classical Poisson brackets. We argue that the usual projection onto the light-front coordinates for these from the covariant commutation ralations does not reproduce the expected results.